Kekuatan Mengikat Perjanjian Internasional dan Hukum Kebiasaan Internasional: Analisis Perbandingan - Monica Viny Angraini; Grace Putri Waghe; Ria Wierma Putri; Le Thi Minh Phuong (Unram Law Review, 2025)
International treaties and customary international law are two main sources in the international legal system. Both have the function of regulating relations between countries and international actors, but there are differences in the mechanisms of formation and its binding force. This study contributes to fill the analytical gap in previous comparative works by examining how legitimacy and enforceability differ under modern international adjudication contexts.Using normative legal research methods, specifically the statute approach and conceptual analysis, an analysis is conducted on the legal principles, doctrines, and practices of states to understand how the legitimacy and effectiveness of both are recognized in the international legal system.. The results of the study show that international treaties generally have more explicit and specific binding force because they are based on the formal agreement of the parties, while customary international law is binding based on general practices accepted as law (opinio juris). However, in certain situations, customary law can apply more broadly, including to countries that are not parties to an agreement. This study emphasizes the importance of understanding the interaction between the two in an effort to maintain legal certainty and stability of international relations.